2022
DOI: 10.1177/03000605221089780
|View full text |Cite
|
Sign up to set email alerts
|

A case of complete atrioventricular block associated with primary cardiac lymphoma reversed without cardiac pacemaker implantation

Abstract: Primary cardiac lymphoma (PCL) is a rare malignant lymphoma that is characteristically confined to the heart and/or pericardium. Here, the case of a 70-year-old male patient with complete atrioventricular block (AVB) associated with PCL is presented. The patient had a 10-month history of palpitation and electrocardiogram (ECG) showed a complete AVB. Additionally, transthoracic echocardiography indicated pericardial effusion where atypical lymphoid cells were identified by pericardiocentesis. Subsequent mediast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In this paper, we noted that the patient presented with dyspnea, edema, multiple serous effusions, hepatic and renal dysfunction, coagulation dysfunction, sinus rhythm, third-degree atrioventricular block, full-lead low voltage, QT interval prolongation, and a borderline escape rhythm. Numerous studies have reported cases of primary cardiac lymphoma accompanied by atrioventricular block (Table 1) (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The age of patients included in these studies ranged from 36.0 to 80.0 years, with 58.3% of them being men.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we noted that the patient presented with dyspnea, edema, multiple serous effusions, hepatic and renal dysfunction, coagulation dysfunction, sinus rhythm, third-degree atrioventricular block, full-lead low voltage, QT interval prolongation, and a borderline escape rhythm. Numerous studies have reported cases of primary cardiac lymphoma accompanied by atrioventricular block (Table 1) (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The age of patients included in these studies ranged from 36.0 to 80.0 years, with 58.3% of them being men.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with pericardial involvement, it may present with pericarditis, pericardial effusion or tamponade. Finally, the tumor affecting the conduction pathways can cause various heart blocks 4–6 …”
Section: Discussionmentioning
confidence: 99%
“…Left atrial tumors such as myxoma may mimic mitral stenosis and cause systemic embolism, while right atrium or right F I G U R E 1 CT shows giant mass filling the atrium and ventricle (Coronal and axial plane) F I G U R E 2 MRI demonstrates giant mass invading myocardium and pericardium (Coronal plane) F I G U R E 3 Mass excised from right atrium and ventricle ventricular tumors may cause pulmonary embolism and right heart failure.In patients with pericardial involvement, it may present with pericarditis, pericardial effusion or tamponade. Finally, the tumor affecting the conduction pathways can cause various heart blocks [4][5][6].…”
mentioning
confidence: 99%